Photoluminescent iron disilicide on modified Si surface by using silver. (30th April 2015) - Akiyama, Kensuke; Motomura, Shinichi; Itakura, Masaru; Naganuma, Yasuhiro; Funakubo, Hiroshi
Abstract: Pronounced enhancement of photoluminescence (PL) intensity was observed from β-FeSi2 by using metal–organic chemical vapor deposition (MOCVD) on (100) Si substrates coated with a silver (Ag) layer. X-ray diffraction analysis revealed modifications to the crystal structure near the surface of Si, where the in-plane lattice parameter had been elongated, by Ag atomic diffusion from the surface to inside the Si during the heating process before deposition. This modified Si surface contributed to decreasing the non-radiative recombination centers at the β-FeSi2 /Si interface and in the β-FeSi2 film, which led to the pronounced enhancement of PL intensity.